Relationship of Diet and Menstrual Cycle with Anemia in Young Women: Hubungan Pola Makan dan Siklus Menstruasi dengan Anemia pada Remaja Putri - Hadriani Hadriani; Christina Entoh; Zakiah Radjulaeni; Meike Dwi Astuti (Poltekkes Kemenkes Palu, 2023)
Background: Anemia is a problem that occurs in young women which results in decreased productivity, mental development, and intelligence. Based on the Indonesian Basic Health Research, the prevalence of anemia in young women has increased from 2013 (22.7%) to 2018 (32%). Objective: to determine the relationship between diet and menstrual cycle with anemia in young women at State Senior High School (SMAN) 7 Palu City. Methods: observational analytic, using a cross-sectional approach. The number of samples is 45 young women with random sampling technique. Data were analyzed by univariate test and bivariate test. Bivariate test analysis using the Chi-Square test. Results: Analysis of the relationship between eating patterns and anemia in female adolescents OR 3.238 (p=0.058). Analysis of the relationship between the menstrual cycle and anemia in young women OR 5.950 (= 0.007). Conclusion: There is an effect of health education with leaflet media on women's knowledge about cervical cancer screening. It is expected that health workers will regularly provide health education